Literature Review of Project Risk Identification in Steel Building Construction - Ariyanto, Ismail Nur (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The steel construction is one of the vital sectors in the development of modern infrastructure and buildings. However, despite the many advantages that this industry has, steel construction contractors are also faced with a number of challenges that require strategies and innovations to overcome. Risk can be defined as the chance of an adverse event occurring, which is caused by the uncertainty of what will be faced. Construction risk management is the process of identifying, assessing, and controlling potential risks that could affect a construction project. This involves analyzing all aspects of a project and implementing strategies to prevent or minimize the impact of these risks. Here are some steps can take to effectively manage risks in construction projects. Using sources based on the previous research, here will be identifying what types of risk factors are most commonly occurs for steel building construction project. The types of risk that will be discussed here will be divided into three types based on internal risk, external risk, and project risk. Each type of risk includes technical and non-technical risks. Based on the data this study identify that internal risk with technical aspects is the most common type of potential risk occurs on steel building construction project.